PENGARUH KARAKTERISTIK PERUSAHAAN, UKURAN PERUSAHAAN, KOMPENSASI KERUGIAN FISKAL, DAN GOOD CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE - Worokinasih, Saparila; Aulya Dhinda Putri, Ridha (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of company characteristics, company size, fiscal loss compensation, and good corporate governance on tax avoidance. In this study, company characteristics are proxied by leverage and good corporate governance is proxied by audit committee and audit quality. The leverage is measured using the debt to total assets (DAR) ratio, profitability is measured using the return on assets (ROA) ratio, company size is measured based on total assets, fiscal loss compensation as a form of tax incentive measured using dummy variables, the audit committee is calculated by the number of audit committees in the company, and audit quality is measured based on the big four kap using dummy variables, and tax avoidance is calculated using Cash ETR. This research uses a quantitative approach with explanatory research. The sample was in 20 energy sector companies for the period 2018-2021. This study uses panel data regression analysis. Based on the results using the chow test and the hausman test, the regression model used is the fixed effect model. The regression results show that leverage, company size, and audit quality affect tax avoidance, while profitability, fiscal loss compensation, and audit committee have no effect on tax avoidance.